(untitled) (Scientific journal of the Fergana State University, 2024)
In this small study describes the theoretical foundations of communication, which plays an important role in human life, as well as the scientific research of scientists in this area. The main purpose of the article is to analyze the views and opinions of world scientists regarding communication in linguistics. This paper used comparison and comparison methods, resulting in examples of research by scientists who have conducted research from the historical development of communication to the present day. Instead of a final word, we present our own opinion while studying the research of world scientists.